Specialists make faster decisions than generalists: experiments with aphids - Bernays, E. A. (1999)
Theoretical studies and a few recent experimental reports suggest that the evolution of diet breadth in herbivorous insects is constrained by a limited neural ability to efficiently process large amounts of information in short periods of time. This neural-constraints hypothesis predicts that generalist herbivores should make slower or poorer decisions than specialists when selecting plants, because generalists must discriminate and decide among stimuli from a wider variety of potential hosts. The present study compares the speed with which host-associated decisions are made in specialist versus generalist populations of the aphid Uroleucon ambrosiae. Populations of U. ambrosiae from eastern North America are highly specific to the host plant Ambrosia trifida (Asteraceae), whereas those from the American southwest also feed on a variety of other taxa from the Asteraceae. Experiments with winged (alate) and wingless (apterous) individuals showed that host-finding, host-selection, host-acceptance, host-sampling and host-settling were more efficiently performed by the eastern specialists. These very consistent results provide evidence that strongly supports the neural-constraints hypothesis.